Raw challenge - Montgomery, Lisa (Hatherleigh, 2013)
"Have you ever wanted to change your diet and eat healthier, fresher foods, but didn't know where to start? Have you ever wanted to see what the raw diet craze is all about, but felt intimidated to begin? If so, The 30-Day Raw Challenge is the book for you! The 30-Day Raw Challenge is an innovative, easy-to-follow lifestyle diet and health program created by raw food expert Lisa Montgomery. Lisa developed The 30-Day Raw Challenge by working with individuals who sought to make needed changes to a healthier diet and did so effortlessly using raw foods. The 30-Day Raw Challenge compiles anecdotes of their transformation to healthier living through a raw food diet as well as a simple step-by-step plan to help you embrace raw foods in your diet. The book also includes daily menus and over 100 simple raw recipes guaranteed to make a positive change in your life. The 30-Day Raw Challenge is a must-have for anyone looking for an effective program for weight loss, healthier living, and longevity"--